Allogenic controls on autogenic variability in fluvio‐deltaic systems: inferences from analysis of synthetic stratigraphy. (24th May 2014) - Karamitopoulos, P.; Weltje, G. J.; Dalman, R. A. F.
Abstract Fluvio‐deltaic stratigraphy develops under continuous morphodynamic interactions of allogenic and autogenic processes, but the role and relative contribution of these processes to the stratigraphic record are poorly understood. We analysed synthetic fluvio‐deltaic deposits of several accommodation‐to‐supply cycles (sequences) with the aim to relate stratigraphic variability to autogenic and allogenic controls. The synthetic stratigraphy was produced in a series of long time‐scale (105 years) numerical experiments with an aggregated process‐based model using a typical passive‐margin topography with constant rates of liquid and solid river discharge subjected to sinusoidal sea‐level fluctuation. Post‐processing of synthetic stratigraphy allowed us to quantify stratigraphic variability by means of local and regional net sediment accumulation over equally spaced time intervals (1–10 kyr). The regional signal was subjected to different methods of time‐series analysis. In addition, major avulsion sites (>5 km from the coastline) were extracted from the synthetic stratigraphy to confirm the interpretations of our analyses. Regional stratigraphic variability as defined in this study is modulated by a long‐term allogenic signal, which reflects the rate of sea‐level fluctuation, and it preserves two autogenic frequency bands: the intermediate and high‐frequency components. The intermediate autogenic component corresponds to major avulsions with a median inter‐avulsion period of ca. 3 kyr. This component peaks during time intervals in which aggradation occurs on the delta plain, because super‐elevation of channel belts is a prerequisite for large‐scale avulsions. Major avulsions occur occasionally during early stages of relative sea‐level fall, but they are fully absent once the coast line reaches the shelf edge and incision takes place. These results are consistent with a number of field studies of falling‐stage deposition in fluvial systems. The high‐frequency autogenic component (decadal to centennial time scales) represents mouthbar‐induced bifurcations occurring at the terminal parts of the system, and to a lesser extent, partial or small‐scale avulsions (<5 km from the coastline). Bifurcation intensity correlates strongly with the rate of progradation, and thus reaches its maximum during forced regression. However, its contribution to overall stratigraphic variability is much less than that of the large‐scale avulsions, which affect the entire area downstream of avulsion nodes. The results of this study provide guidelines for predicting fluvio‐deltaic stratigraphy in the context of co‐existing autogenic and allogenic processes and underscore the fact that the relative importance and the type of autogenic processes occurring in fluvio‐deltaic systems are governed by allogenic forcing.